Don Antonio Rimoldi e la trasmissione della cultura storico-religiosa alle giovani generazioni attraverso le tesi su Chiesa e società ambrosiane - Bressan, Edoardo (La Scuola Cattolica, 2025)
The contribution exposes an original aspect of the cultural activity of A. Rimoldi, in accompanying the preparation of different thesis. In addition to demonstrating the areas of research the author highlights the sources used, the acquired results thanks to his expert guide, the slopes of open inquiry and further ahead. This witness shows the educational capacity exerted by A. Rimoldi and his generosity in promoting the publication, in whole or in part, of various theses from him followed.